Report on marine geomagnetic measurements made during research cruises MSM88-1 and MSM88-2 on the German RV Maria S. Merian - Heinrich Villinger; Christian Hübscher; Nico Augustin; Colin W Devey; Anne-Cathrin Wölfl (PANGAEA, 2023)
Part of the UN Decade of Ocean Science for Sustainable Development is the Nippon Foundation-GEBCO Seabed 2030 Project. Its goal is to collect all available bathymetric data, promote large-scale bathymetric mapping projects, and produce a definitive bathymetric map of the oceans by 2030. The expeditions MSM88/1 and MSM88/2 are a German contribution to this international project. The aim of the cruise is described in detail in the cruise report of MSM88 (Devey et al., 2020). The large area (about 300 000 km2) between 14? and 17? North stretching from Cape Verde to the EEZ of Guadeloupe and Martinique was mapped during two legs of expedition MSM88 on the German research vessel Maria S. Merian (Figure 1.1). Leg MSM88/1 started on November 28, 2019 in Mindelo (Cape Verde) and ended also there on December 17, 2019. The second leg, MSM88/2, began on December 19, 2019 in Mindelo and ended in Bridgetown (Barbados) on January 14, 2020. On all 6 profiles, bathymetry, magnetic and sub-bottom data were collected (Figures 1.2 and 1.3 in the Report). Five of the profiles run all across the Atlantic with a length of about 3200 km and cross the the mid-Atlantic Ridge (MAR), which is located at about 46? 37 extquotesingle West. One profile from west to east just crossed the MAR but could not be extended further east due to time constraints. You can find details of the cruise in the cruise report (Devey et al., 2020). A short report describes the processing of the magnetic survey and shows the main results. All data shown can be found at Pangaea repository.